Altered immune cell profiles in blood of mature/peripheral T-cell leukemia/lymphoma patients: an EuroFlow study - Morán-Plata, F. Javier; Muñoz-García, Noemí; Barrena, Susana; Yeguas, Ana; Balanzategui, Ana; Carretero-Domínguez, Sonia; Lécrevisse, Quentin; González-González, María; Mateos, Sheila; Silos, Lidia; Alcoceba, Miguel; Solano, Fernando; et al. (Frontiers in Immunology, 2025)
IntroductionThe interactions between T-cell chronic lymphoproliferative disorder (T-CLPD) tumor cells and the bystander immune cells may play a critical role in the failure of immune surveillance and disease progression, but the altered blood immune profiles of T-CLPD remain unknown.MethodsHere we analyzed the distribution of residual non-tumoral immune cells in blood of 47 T-CLPD patients -14 T-prolymphocytic leukemia (T-PLL), 7 Sézary syndrome/mycosis fungoides (SS/MF) and 26 T-large granular lymphocytic leukemia (T-LGLL)-, as tumor models of neoplastic T-cells that resemble naive/central memory (N/CM), memory and terminal effector T-cells, respectively, compared to 110 age- and sex-matched healthy donors, using spectral flow cytometry.ResultsOverall, our results showed deeply altered immune cell profiles in T-PLL, characterized by significantly increased counts of monocytes, dendritic cells, B-cells, NK-cells and innate lymphoid cells (ILC) -particularly ILC3-, together with reduced normal T-cells. In contrast, SS/MF showed neutrophilia, associated with decreased numbers of dendritic cells and NK-cells, potentially reflecting their increased migration from blood to the skin. In turn, T-LGLL displayed the mildest immune impairment, dependent on the TCD4+ vs. TCD8+ nature of the clonal T-cells and presence of STAT3 mutations among TαβCD8+ T-LGLL cases. Further dissection of the normal T-cell compartment showed a significant reduction of the earliest T-cell maturation compartments (N/CM) in T-PLL and SS/MF, whereas T-cells remained within normal ranges in T-LGLL, with only a minor reduction of N/CM T-cells.ConclusionThese findings point out the existence of differentially altered innate and adaptive immune cell profiles in the distinct diagnostic subtypes of T-CLPD, with progressively less pronounced alterations from T-PLL and SS/MF to T-LGLL.